The Effectiveness of Clicker-Assisted Peer Instruction on Improving High School Students' Understanding of Electromagnetism Concepts - Doni Nurdiansyah; Chaerul Rochman; Anna Permanasari (Green Publisher Indonesia, 2026)
Electromagnetism is a fundamental yet challenging topic in high school physics, as students often struggle to develop deep conceptual understanding through conventional lecture-based instruction. This study aims to examine the effectiveness of clicker-assisted Peer Instruction (PI) in improving students’ understanding of electromagnetism concepts. A quasi-experimental pretest–posttest control group design was employed involving two intact grade-11 classes (N = 58). The experimental group was taught using Peer Instruction supported by clickers, while the control group received conventional lecture-based instruction over a four-week period. Data were collected using a 25-item conceptual test with a reliability coefficient (KR-20) of 0.82. Data analysis included descriptive statistics, independent-samples t-test, ANCOVA with pretest scores as covariates, and effect size calculation using Hedges’ g. The results show that the experimental group achieved a significantly higher normalized gain (〈g〉 = 0.62) compared to the control group (〈g〉 = 0.35). Statistical analysis revealed a highly significant difference between groups (p < 0.001) with a very large effect size (Hedges g = 1.64). The findings indicate that clicker-assisted Peer Instruction not only enhances conceptual understanding but also reduces performance variability among students. In conclusion, the integration of clickers within the Peer Instruction framework is highly effective in improving students’ conceptual mastery of electromagnetism. This approach is recommended as an alternative instructional strategy to promote active learning and meaningful engagement in physics education.